Fortress or house of cards? A comparative, critical analysis of Australia’s and New Zealand’s COVID-19 vaccination rollout - Wolf, Katharina; Petra, Theunissen (Public Relations Institute of Australia, 2023)
This research provides critical, comparative insights into Australia and New Zealand’s public communication approaches associated with the initial rollout of the COVID-19 vaccine, hailed as a crucial element of both countries’ recovery and reconnection to the rest of the world. Although Australia and New Zealand share similar socio-political contexts, the two countries approached the rollout very differently. Applying the circuit of culture model, this study explores the second year of the global COVID-19 pandemic through an Oceania lens, providing critical insights into the unique opportunities afforded to the island nations, as well as their exposure to global challenges. This paper aims to provide insights and learnings that may shape future responses to global (health) emergencies, including a call to rethink the notion of time-bound (public) communication campaigns in complex, ever-changing environments.